Developing negative split pacing in endurance athletes: practical guidelines and training models - Grivas, Gerasimos V.; Safari, Kousar; Hemmatinafar, Mohammad (Frontiers in Physiology, 2026)
Negative split pacing—finishing the second half of a race faster than the first—is a hallmark of elite endurance performance and a key indicator of physiological control, fatigue resistance, and strategic pacing literacy. Rather than being an inherent talent, it represents a trainable skill integrating physiological, cognitive, and behavioral regulation. This mini review synthesizes evidence from performance analyses, physiological studies, and coaching practice to outline how negative split capacity can be systematically developed. We summarize training foundations, mesocycle design, and monitoring tools that support its acquisition. Mechanistically, successful negative splits are linked to improved lactate threshold (LT), VO2 kinetics, running economy (RE), central fatigue resistance, and pacing awareness. Practically, progression runs, split-pace long runs, and interval ladders promote these adaptations through controlled exposure to fatigue and deliberate perceptual feedback. A 6-week exemplar mesocycle illustrates how structured planning with pace anchors and feedback loops (HRV, GPS, session-RPE) refines pacing control and race execution. Psychological skills—including attentional focus, restraint, and adaptive decision-making—are essential to resist early surges and preserve finishing capacity. While negative split pacing may be constrained in short/middle-distance events, heat, altitude, or tactical racing, in endurance road events it offers a robust, learnable performance model. Overall, negative split pacing is not merely an outcome of elite talent but a trainable strategy rooted in physiology, cognition, and feedback-informed coaching. With deliberate practice and individualized monitoring, athletes across levels can enhance consistency, resilience, and race-day outcomes.